Strengthening the Development of Smoked Fish Processing Business in Galala Village - talakua, jeanete (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The high potential of fishery resources in Ambon City has contributed to the community’s habit of consuming fish, both in fresh and processed form. The most famous processed fish in Ambon City is smoked fish (locally known as ikan asar), whose production center is located in Galala Village. Smoked fish processing is classified as a home industry-scale business. Therefore, limited resources require arrangements that can optimize their use and solve the problems faced in the processing business. This article discusses the potential and conditions as well as problems faced in the development of smoked fish processing businesses, empowering fishermen to develop independent and sustainable smoked fish processing businesses. The results show that there is a lot of fisheries potential in Galala Village, but the weak development of smoked fish business is due to limited access to capital and management, no training to support smoked fisheries processing, especially in the application of sanitation, hygiene, good packaging and durability, no business expansion or development, weak networks and business partnerships and not intensive assistance and supervision. Empowerment of smoked fish processing fishermen is carried out in a participatory manner by considering the potential, problems and needs of fishermen business owners.